550 of 'Cassell's History of the War between France and Germany.... - The British Library (Wikimedia Commons, 2013)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Licence No known copyright restrictions via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons